Comparative 3D micro‐CT and 2D histomorphometry analysis of dental implant osseointegration in the maxilla of minipigs. (27th February 2017) - Bissinger, Oliver; Probst, Florian Andreas; Wolff, Klaus‐Dietrich; Jeschke, Anke; Weitz, Jochen; Deppe, Herbert; Kolk, Andreas
Abstract: Aim: The bone implant contact (BIC) has traditionally been evaluated with histological methods. Thereupon, strong correlations of two‐dimensional (2D) BIC have been detected between μ CT and destructive histology. However, due to the high intra‐sample variability in BIC values, one histological slice is not sufficient to represent 3D BIC. Therefore, our aim has been to correlate the averaged values of 3–4 histological sections to 3D μ CT. Material and Methods: Fifty‐four implants inserted into the maxilla of 14 minipigs were evaluated. Two different time points were selected to assess the 3D BIC (distance to implant: 2–5 voxels), an inner ring (6–30 voxels) and an outer ring (55–100 voxels) using μ CT (voxel size: 10  μ m) and to correlate the values to histomorphometry. Results: Strong correlations ( p  < 0.0001; 28 days, 56 days, total) were seen between μ CT and histomorphometry concerning BIC ( r  = 0.84, r  = 0.85, r  = 0.83), the inner ring ( r  = 0.87, r  = 0.87, r  = 0.88) and the outer ring ( r  = 0.85, r  = 0.85, r  = 0.88). Closer to the implant, μ CT values were higher compared with histomorphometry. Conclusion: Although 3–4 histological slices per implant seem to predict the 3D BIC, μ CT might be advantageous because of its non‐destructive 3D character. The healing time may not impact on the comparability.